The night season [compact disc, unabridged] - Cain, Chelsea (Cain, Chelsea. Archie Sheridan/Gretchen Lowell novel., 2011)
Now that serial killer Gretchen Lowell is locked away, Portland detective Archie Sheridan is looking forward to a break from work. However, the city is in the midst of a bad flood, which has claimed the lives of several people. And when the coroner rules that one of the victims died from poisoning, Sheridan discovers that the city has fallen prey to a new killer, one which has been using drownings to mask his murder for several years.